Sistem Nilai Budaya Dalam Tradisi Kasesenan Di Suku Tounsawang Minahasa - Militia Kristi Walangitan; Rama Tulus Pilakoannu; David Samiyono (Universitas Negeri Medan, 2020)
In the Tounsawang tribal community the mapalus tradition in death (about eating together) is known as kasesenan. The tradition of kasesenan is a meeting place for families, brothers and sisters to help and help as a form of togetherness with a bereaved family. The purpose of this study was to analyze the understanding of the Tounsawang Minahasa community regarding the implementation of the past and present of the kasesenan and analyze the cultural value system contained in its implementation. The author uses the theory of collective awareness, cultural value systems and understanding eating together. This study uses a qualitative-descriptive research approach to collect data that is in accordance with what researchers need from the Tounsawang Minahasa community. The results of the study revealed that the existence of the kasesenan tradition is still being carried out and in the implementation of this tradition has experienced some changes but this change without leaving the value of the kasesenan itself even this tradition becomes the glue of social loyalty in people's lives such as the Minahasa slogan 'We Are All Brothers'. Thus, it is the collective memory of the people that keeps the culture of Kasesenan still maintained today. This culture is capable of giving birth to values such as mutual acceptance, fostering a sense of togetherness in society, solidarity, brotherhood, sharing, glue of social loyalty, mapalus, loyalty to ancestral traditions, and cultural preservation.